2004
DOI: 10.7326/0003-4819-140-12-200406150-00009
|View full text |Cite
|
Sign up to set email alerts
|

Drug Provocation Tests in Patients with a History Suggesting an Immediate Drug Hypersensitivity Reaction

Abstract: Drug provocation tests in individuals with suspected drug allergy performed in carefully controlled settings can confirm drug hypersensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
209
3
9

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(240 citation statements)
references
References 12 publications
18
209
3
9
Order By: Relevance
“…It is well known that most patients with a suspected drug allergy have negative responses in skin and challenge tests. This is true for adults 21 and for children. In a Portuguese study, only 7% of the children with a self-reported drug allergy had a confirmed diagnosis.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…It is well known that most patients with a suspected drug allergy have negative responses in skin and challenge tests. This is true for adults 21 and for children. In a Portuguese study, only 7% of the children with a self-reported drug allergy had a confirmed diagnosis.…”
Section: Discussionmentioning
confidence: 75%
“…10,24 We should note that the frequency of positive tests to betalactams found in the present study is similar to the results reached in adult studies. 21,25 Despite the lower incidence of all positive DPT in the group skin tested, they have a higher time delay to the diagnosis than the non-skin tested group. That could be due to the fact that skin tests to betalactams are not readily available and a ''waiting strategy'' was taken in skin-tested children in order to achieve an older age.…”
Section: Discussionmentioning
confidence: 94%
“…More recent European studies reported that between 8.4% [154] and 30.7%, skin test-negative patients reacted on drug challenge only. In the study by Messaad and colleagues [154], only 23% were positive for major and minor determinants and 46.3% skin test positive to the specific beta-lactam (but not PPL/MDM), indicating that only 69.3% were diagnosed by skin testing and 30.7% diagnosed following drug provocation [155].…”
Section: Predictive Value Of Skin Tests For Penicillinmentioning
confidence: 99%
“…Entretanto, todos os esquemas são definidos com base no aumento progressivo das concentrações do medicamento a ser administrado, iniciandose por amostras muito diluídas e concluindo-se o processo com preparados em diluições similares às que serão utilizadas (Tabela 4). No caso da penicilina, a dessensibilização é indicada quando não houver possibilidade de substituição do medicamento 20,21,31 .…”
Section: O Diagnóstico De Alergia Foi Confirmado E a Dessensibilização?unclassified
“…Portanto, ao se optar pela realização de um teste alérgico, deve-se utilizar o produto adequado. Deve-se salientar que os testes são úteis somente para as reações que envolvem anticorpos da classe IgE, não tendo valor preditivo para as reações do tipo exantema tardio, febre, anemia hemolítica, dermatite exfoliativa, síndrome de Stevens-Johnson, dermatite de contato, nefrite intersticial ou doença do soro 8,20 .…”
Section: S181 Introduçãounclassified